Tổng hợp và cấu tạo của một số dẫn xuất xeton-α,β-không no chứa nhân dị vòng furan, pirol, thiophen và piridin - Triệu, Nguyễn Đình; Hà, Vũ Văn (Vietnam Journal of Chemistry, 2012)
Some derivatives of 2-furyl-, 2-thienyl-, 2-N-methylpyrrolyl-, 2- and 3-pyridyl-arylvinyl ketones have been synthesized by the condensed reaction of methylketones with the heterocyclic aldehydes. Their structure was identified by IR, 1H- and 13C spectra. The chargedensities on the carbon atoms of the main molecular skelete of 1-phenyl-, 1-(p-bromphenyl)- and 1-(p-methylphenyl)-3-(2’-thienyl)-pro-2-en-1-one have been computed using chemical quantum AM1.